2008
DOI: 10.1074/jbc.m710592200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of a Functional Dimer of the PhoQ Sensor Domain

Abstract: The PhoP-PhoQ two-component system is a well studied bacterial signaling system that regulates virulence and stress response. Catalytic activity of the histidine kinase sensor protein PhoQ is activated by low extracellular concentrations of divalent cations such as Mg 2؉ , and subsequently the response regulator PhoP is activated in turn through a classic phosphotransfer pathway that is typical in such systems. The PhoQ sensor domains of enteric bacteria contain an acidic cluster of residues (EDDDDAE) that has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
128
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(145 citation statements)
references
References 43 publications
14
128
0
3
Order By: Relevance
“…1d). Differences observed between these domains have recently been pointed out by Cheung et al (1). They suggested that these domains comprise a fold "distinct from the PAS domain structures with which they share a ␤-sheet topology" and named them "PDC" fold based on previously determined structures (PhoQ, DcuS, CitA).…”
mentioning
confidence: 99%
“…1d). Differences observed between these domains have recently been pointed out by Cheung et al (1). They suggested that these domains comprise a fold "distinct from the PAS domain structures with which they share a ␤-sheet topology" and named them "PDC" fold based on previously determined structures (PhoQ, DcuS, CitA).…”
mentioning
confidence: 99%
“…Low cation concentrations promote activation of mgtA, pbgC, pcgF, pcgG, mgtCB, and psiD genes whereas high concentrations result in the repression of these genes [47,48]. These results indicate that Salmonella PhoQ is a sensor for periplasmic concentrations of divalent cations.…”
Section: Ax21 Is Predicted To Be An Inducer Of Densitydependent Gene mentioning
confidence: 50%
“…These results indicate that Salmonella PhoQ is a sensor for periplasmic concentrations of divalent cations. The role of divalent cations as signals for PhoQ is also supported by the crystal structures of the PhoQ periplasmic sensor domains from S. typhimurium and E. coli [48]. Similarly, we have shown that the Xoo PhoPQ system is required for sensing low extracellular Mg 2+ and Ca 2+ concentrations, conditions that the pathogen likely is confronted with upon entry into the xylem of the rice plant [33].…”
Section: Ax21 Is Predicted To Be An Inducer Of Densitydependent Gene mentioning
confidence: 57%
“…The majority of previously characterized SDs adopt two main types of structural scaffolds, the PAS-like and four-helix bundle domains. A PASlike (16) or "PDC" fold (17) is represented by the structures of PhoQ (17,18), DcuS (19), and CitA (16). The double PAS-like domain has also been observed in LuxQ (20), DctB (21,22), and in recently reported KinD (23).…”
mentioning
confidence: 88%